Self Efficacy dapat Meningkatkan Manajemen Perawatan Luka Gangren pada Pasien Diabetes Mellitus - Wikantana, Wikantana (Journal of Management Nursing, 2022)
Introduction: Self Efficacy affects how a person thinks, feels self-motivated, and acts. Beliefs encourage self-control processes to maintain the behaviors needed to administer care. High self-confidence in diabetes mellitus patients is needed so that they have confidence and success in carrying out independent management. Individuals with high self-efficacy will be able to manage symptoms, treatment, physical changes, and lifestyle to adapt to their conditions. Objectives: This study aims to determine the relationship between self-efficacy and management of gangrenous wound care in patients with diabetes mellitus. Method: This type of research is quantitative with a cross-sectional approach. The design in this study used a correlation or correlation study with a total sampling of 40 respondents at the Bogor City Hospital. The instrument used was the Self Efficacy and Wound Care Management questionnaire sheet, which consisted of 40 questions. Then the data were analyzed using the Chi-Square test. Result: The results of the analysis obtained a p-value = 0.022 which means p-value < 0.05 in other words there is a significant relationship between Wound Care Management and Self Efficacy. Conclusion: This study concludes that there is a relationship between self-efficacy and management of gangrene wound care in patients with diabetes mellitus.